2022
DOI: 10.3389/frsen.2021.767593
|View full text |Cite
|
Sign up to set email alerts
|

An Operational Methodology for Validating Satellite-Based Snow Albedo Measurements Using a UAV

Abstract: Snow albedo is highly variable over multiple temporal and spatial scales. This variability is more pronounced in areas that experience seasonal snowpack. Satellite retrievals, physically based models and parameterizations for snow albedo all require ground-based measurements for calibration, initialization, and validation. Ground measurements are generally made using upward and downward-facing pyranometers at opportunistically located weather stations that are sparsely distributed, particularly in mountainous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…There have been case studies, though, that have demonstrated mapping of broadband albedo in snow-covered environments. These studies have used paired pyranometers mounted in upward-and downward-looking configurations (Webster and Jonas, 2018;Sproles et al, 2020;Mullen et al, 2022) or a single downward-looking pyranometer on the UAV and a stationary upward-looking pyranometer within the flight area (Levy et al, 2018). These measurements return a single spectrally integrated value for incident and reflected radiation, from which broadband albedo can be calculated.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been case studies, though, that have demonstrated mapping of broadband albedo in snow-covered environments. These studies have used paired pyranometers mounted in upward-and downward-looking configurations (Webster and Jonas, 2018;Sproles et al, 2020;Mullen et al, 2022) or a single downward-looking pyranometer on the UAV and a stationary upward-looking pyranometer within the flight area (Levy et al, 2018). These measurements return a single spectrally integrated value for incident and reflected radiation, from which broadband albedo can be calculated.…”
Section: Previous Workmentioning
confidence: 99%
“…These measurements return a single spectrally integrated value for incident and reflected radiation, from which broadband albedo can be calculated. If care is taken to fly only over snow, this would be an effective snow albedo (Mullen et al, 2022), otherwise, snow cannot be separated from other land surface types with a spectrally integrated measurement. Rather, the goal is to measure mixed land surfaces to understand heterogeneity when snow is present with other land surface types (Webster and Jonas, 2018).…”
Section: Previous Workmentioning
confidence: 99%